Ultrasound imaging of immersed plates using high-order Lamb modes at their low attenuation frequency bands - Takiy, Aline E. (2017)
This paper focuses on the use of a Lamb wave-based methodology for ultrasound imaging of immersed plate structures. In these cases Lamb waves can be strongly attenuated due to leaky waves and viscous losses in the liquid, but there are low attenuation frequency bands that may be used for NDT applications. Experimental measurements were conducted to validate the existence of these low attenuation frequency bands, which were also theoretically predicted for some propagation modes, between the frequencies-thickness products of 0.5 MHz mm and 9.0 MHz mm. Using a 5 MHz linear-array and phased-array techniques, A1 and S1 modes are used to obtain images of an immersed aluminum plate with artificial defects. The signals are post-processed in order to select the desired propagation mode and to obtain an image with dynamic focusing in reception. While the A1 mode is strongly attenuated, the S1 mode, at 3.4 MHz mm, can be used to detect and localize defects in the immersed plate.